The Role of Carvedilol in the Treatment of Dilated and Anthracyclines-Induced Cardiomyopathy - Makoto Kodama; Kenji Suzuki; Somasundaram Arumugam; Rajarajan A. Thandavarayan; Kenichi Watanabe; Wawaimuli Arozal; Flori R. Sari (MDPI AG, 2011)
Although chronic sympathetic activation provides inotropic and chronotropic support to the failing heart, such activation may also have deleterious effects, including the direct cardiotoxic effects of catecholamines, activation of the renin-angiotensin-aldosterone system and an increase in myocardial oxygen demand. These observations indicate that β-blockade might be beneficial in the treatment of heart failure resulting from dilated cardiomyopathy or ischaemic heart disease. Carvedilol is a non-selective β-blocker acting on β1-, β2-, and α1-adrenoceptors. It possesses potent anti-oxidant and anti-apoptotic properties, along with neuroprotective, vasculoprotective, cardioprotective effects, and it has reduced overall mortality in patients with heart failure in controlled clinical trials. Its role in treating cardiomyopathy requires focus. The fact that anthracyclines are cardiotoxic seriously narrows their therapeutic index in cancer therapy. The cardiotoxic risk increases with the cumulative dose and may lead to congestive heart failure and dilated cardiomyopathy in adults and in children. This review focuses on recent research regarding the beneficial effects of carvedilol in the treatment of dilated cardiomyopathy and to revisit the available evidence on the cardioprotection of carvedilol when associated with anthracycline and to explain the mechanisms underlying the benefits of their co-administration.